Incidencia de la implementación del proyecto “Transporte Seguro” en el servicio de buses de transporte público urbano de la ciudad de Loja, 2015 - David Israel, Valle Curipoma (2017)
This research work, entitled IMPACT OF THE IMPLEMENTATION OF "SAFE TRANSPORT" PROJECT IN THE SERVICE OF BUSES OF TRANSPORT PUBLIC URBAN FROM THE CITY OF LOJA, 2015 ", it was taking into account each of the stages of the investigative process, and according to the guidelines which provides the regulation of the academic regime of National University of Loja. The purpose of this research is to determine the impact of the implementation of the Safe Transport project, which aims to reduce delinquency rates and improve citizen safety, in the urban transportation buses of the city of Loja, with the aim of finding Response in terms of safety in this public transport, so it can be said that due to the opinions of users when making use of this service, there is insecurity in this means of transport. The objectives were fulfilled, with the purpose of giving a contribution to knowledge, starting with the collection of information regarding theoretical contents and application of different research techniques. After applying the research techniques, it was verified that the 238 existing urban transport buses in the city of Loja already have the implementation of the Safe Transport project. But despite its implementation, criminal acts such as robbery and theft are still occurring in this means of transport and its main causes for committing these crimes are excessive excess passengers, carelessness and distraction of the user towards his Around, and display of valuables. Regarding the socialization and dissemination of the Safe Transport project by the different means of communication, it has been null. And the National Transit Agency as the entity in charge of the implementation of this project is who should do it, since there is a total ignorance of the content and application of the same by the citizens of the Lojana.